Historia i rozwój leczenia bólu - przegląd wiedzy na temat postępowania analgetycznego od starożytności do czasów współczesnych = History and development of pain treatment - the literature review about analgetic procedures from antiquity to present day - Główczewska-Siedlecka, Emilia; Mądra-Gackowska, Katarzyna; Nowacka, Krystyna; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2016)
Główczewska-Siedlecka Emilia, Mądra-Gackowska Katarzyna, Nowacka Krystyna, Kędziora-Kornatowska Kornelia. Historia i rozwój leczenia bólu - przegląd wiedzy na temat postępowania analgetycznego od starożytności do czasów współczesnych = History and development of pain treatment - the literature review about analgetic procedures from antiquity to present day. Journal of Education, Health and Sport. 2016;6(9):479-488. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.151626 http://ojs.ukw.edu.pl/index.php/johs/article/view/3870 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 16.09.2016. Historia i rozwój leczenia bólu - przegląd wiedzy na temat postępowania analgetycznego od starożytności do czasów współczesnych History and development of pain treatment - the literature review about analgetic procedures from antiquity to present day Główczewska-Siedlecka Emilia1, Mądra-Gackowska Katarzyna1, Nowacka Krystyna2, Kędziora-Kornatowska Kornelia1 1. Katedra i Klinika Geriatrii, Collegium Medicum im. L. Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2. Katedra i Klinika Rehabilitacji, Collegium Medicum im. L. Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu Streszczenie Zagadnienie leczenia bólu stanowi od zarania dziejów istotną część medycyny. Od czasów najdawniejszych ludzie starali się zwalczać ból za pomocą środków farmaceutycznych, zabiegów fizykalnych i procedur zabiegowych. Postępowanie z bólem ewoluowało od czasów starożytnych aż po model współczesny charakteryzujący się multidyscyplinarnym podejściem i tworzeniem się specjalistycznych centrów leczenia bólu. W niniejszej publikacji dokonano przeglądu literatury celem ukazania historii i rozwoju leczenia bólu na tle historii medycyny oraz oceny jak wydarzenia z historii Świata takie jak na przykład konflikty zbrojne wpływały na podejście do leczenia bólu. Słowa kluczowe: leczenie bólu, historia medycyny, leki przeciwbólowe Abstract Pain treatment presents important part of history of medicine from primaeval times. Since these times people always tried to treat pain by the use of drugs, physical factors or operative procedures. Pain treatment has evolved since antiquity to present day, when modern model of pain treatment consist on multidisciplinary approach and creation of specialistic pain treatment centers. This publication relies on the review of literature about pain treatment history. This publication show relaitons beetwen history of pain treatment and general history of medicine and also general history of World for example association beetwen wars and military conflicts and development of pain treatment procedures. Key words: pain treatment, history of medicine, analgetic drugs